RESILIENCY OF WOMEN SURVIVORS OF THE TSUNAMI 2004 IN SOUTH INDIA - Jude, Gonsalvez; Miriam, Samuel; Prince, Solomon (European Scientific Journal, ESJ, 2013)
This is a research study on wives of the fishermen who lost their lives in the Tsunami of 2004. It utilizes the qualitative and some Quantitative data. It focuses on the strengths based approach. The study presents an understanding of the survivors’ thoughts on their resiliency and provides suggestions for improving social work practice and education. Resiliency is not a new concept. Researchers have tried to understand this human tendency to strive for a healthier and more positive development for approximately the last 50 years. The strengths perspective in the practice of social work has been a long-standing form of approach of social workers towards helping clients. By examining the subjects’ thoughts on their resiliency, it is possible to develop theory and prove the existing theories in terms of this strength based approach in social work. This study in a way is a follow up of the disaster close to eight years after the event. Researchers often place emphasis, and focus their research and discussions on the disaster itself and its immediate impact on the community (Kalayjian, 1999) rather than what happens after that. This study bridges the gap in knowledge by identifying how women survivors of the Tsunami have exhibited resilience in south Indian villages.